Checklist of the family Nymphalidae (Lepidoptera: Papilionoidea) from Myanmar - Jong Bong Choi (Elsevier, 2021)
Mostly southeast Asian countries are known as the area of biodiversity’s hotspot; nevertheless, there are lots of uncleared distributional information and taxonomic errors in insect biodiversity. To resolve and advance the basic data in the species of Lepidoptera from Myanmar, checklist of the family Nymphalidae is provided. As a result, 529 species (included subspecies) of 105 genera in 13 subfamilies of Nymphalidae are listed from Myanmar based on the recent updated taxonomic data and original descriptions.